33 Increased Expression of hsa-let-7f-5p, hsa-miR-221-3p and hsa-miR-31-5p Correlates With Chemoresistance in Carcinoma of the Esophagogastric Junction. (11th January 2018) - Knief, Juliana; Just, Christina; Lazar-Karsten, Pamela; Petrova, Ekaterina; Wellner, Ulrich; Röcken, Christoph; Hummel, Richard; Thorns, Christoph
Abstract: Objectives: The incidence of carcinomas of the esophagogastric junction has increased over the last decades. Neoadjuvant chemotherapy is regularly implemented, but patients' response varies greatly, some cases showing no therapeutic effect, being deemed chemoresistant. Small, noncoding RNAs—miRNAs—have evolved as key players in biological processes, including malignant diseases, promoting tumor growth and expansion via cell dissociation, invasion, migration, and proliferation. Additionally, specific miRNAs (hsa-miR-21, hsa-miR-181b, hsa-miR-221/222) have been implicated in the development of chemoresistance through evasion of apoptosis, cell cycle alterations, and drug target modification. As data concerning chemoresistance in carcinomas of the esophagogastric junction are still scarce, our study aimed to further contribute to the knowledge for this entity. Methods: A retrospective study of 33 patients receiving neoadjuvant chemotherapy was performed. Histologic tumor regression was evaluated using resection specimens, while miRNA profiles were prepared using preoperative biopsies. A preselected panel of 96 miRNAs, known to be of importance in malignancies, was used to test for significant differences between responsive (chemosensitive) and non-responsive (chemoresistant) cases. All data were normalized with GenEx Software Version 6.1 (MultiDAnalyses, Germany) and further analyzed using SPSS Version 22 (IBM, Germany) applying Mann-Whitney-U test for unpaired samples. A P -value < .05 was considered to be statistically significant. Results: After histologic examination, the cohort consisted of 12 non-responders and 21 responders with the following four miRNAs differentially expressed between both groups: hsa-let-7f-5p, hsa-miR-221-3p, hsa-miR-31-5p and hsa-miR-191-5p. The former three showed up-regulation in chemoresistant cases ( P -values .025, .04, and .033) while the latter showed up-regulation in chemosensitive cases ( P -value .014). Conclusion: In conclusion, we identified a panel of three miRNAs predicting chemoresistance as well as a single miRNA contributing to chemosensitivity. These miRNAs might function as prognostic biomarkers and enable clinicians to better predict the effect of or more reliably select patients benefitting from (neoadjuvant) chemotherapy.